LEVELS OF VITAMIN A IN SOME FORTIFIED VEGETABLE OILS AND MARGARINES SOLD IN GOMBE STATE - S.M., MADAKI; M.B., SANI; A.A., ALIYU; JAMILA, AMINU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
This research assessed the levels of compliance with vitamin A fortification by the manufacturers of margarines and vegetable oils. This was carried out by the determination of vitamin A in the margarines and vegetable oil samples which were purchased from retail outlets in Gombe metropolis. The levels of vitamin A were determined calorimetrically at 620nm after extraction. The levels of vitamin A in the vegetable oils samples ranged between 5322 and 7900 iu/kg while the level of margarine samples ranged from 3660-6170 iu/kg and the levels in which is in line with the manufacturers intended level of fortification. However, the recommended value for Vitamin A is 20000 iu/kg. It can be concluded that the degree of compliance in vitamin A fortification in margarine and vegetable oil samples is low and more effort has to be put by authorities to ensure strict compliance by the manufacturers of these products.